2010
DOI: 10.1002/jclp.20709
|View full text |Cite
|
Sign up to set email alerts
|

Culturally relevant family‐based treatment for adolescent delinquency and substance abuse: understanding within‐session processes

Abstract: Identifying psychotherapy processes that likely contribute to client outcome with ethnic minorities is a vital practice and research need, particularly within family-focused, evidence-based treatments (EBT) for youth with externalizing problems. Identifying process variables within a cross-cultural context may improve the efficacy of EBTs by informing psychotherapists how to modify their behavior when working with ethnically diverse clients. The authors described one approach to the development of culturally c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Some caregivers described being indifferent to the ethnicity of the therapist, providing they were professional and respectful in their approach. This is supported by Cunningham and his colleagues (), in a study of African American and Caucasian therapists and caregivers, who found a variety of therapist behaviours that may enhance family engagement regardless of race, racial match between therapist and caregiver, and socio‐economic status of caregiver. These included focusing on strengths and supporting specific positive changes.…”
Section: Discussionmentioning
confidence: 78%
“…Some caregivers described being indifferent to the ethnicity of the therapist, providing they were professional and respectful in their approach. This is supported by Cunningham and his colleagues (), in a study of African American and Caucasian therapists and caregivers, who found a variety of therapist behaviours that may enhance family engagement regardless of race, racial match between therapist and caregiver, and socio‐economic status of caregiver. These included focusing on strengths and supporting specific positive changes.…”
Section: Discussionmentioning
confidence: 78%
“…In the case of substance use, culture can influence familial views for causes, responses, assistance, enabling, and personal responsibility (Cunningham et al, 2010; Hongjie et al, 2010). Integrating cultural values into traditional psychotherapeutic and psychopharmacologic treatments for substance abuse, such as cognitive behavioral therapy, motivational interviewing, acceptance and commitment therapy, and medication therapies such as methadone, Suboxone, and Antabuse, can greatly improve the effectiveness of future interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is clear from the literature that these traditional values cut both ways. While described in the literature (Amaro et al, 2006; Brisson, Roll, & East, 2009; Cloud & Granfield, 2008; Cuadrado & Lieberman, 2002; Cunningham, Foster, & Warner, 2010; DeLaCancela & Martinez, 1983; Delgado, 2007; Gil et al, 2004; Higgs et al, 2008; Smith et al, 2009; Torres et al, 2002; Unger et al, 2002; Valdez et al, 2008), this dynamic has not received a name, and it has rarely been studied in an IDU population. The authors of this article use the term “Dichotomization of cultural values paradigm” to refer to this phenomenon, described extensively in the discussion section.…”
Section: Literature Reviewmentioning
confidence: 99%
“…16 Thus, learning about the role that familism may play in the development of ASB can inform preventive intervention strategies, particularly among Hispanic youth, but possibly among other racial/ethnic backgrounds as well. While current empirically supported therapies mainly focus on relevant systemic factors that exacerbate or maintain the child/adolescent problem, 17 it is possible that conveying familism values to the younger children (who are building a moral system based on their families) - such as being available when a family member has a problem, or knowing that one can talk with family members to share difficulties in life - may facilitate the development of empathy, bonding and attachment to family members, all of which are protective against ASB. 18 …”
Section: Introductionmentioning
confidence: 99%